Analisis Kinerja Keuangan Berdasarkan Rasio Profitabilitas Pada PT. Pinus Merah Cabang Baturaja - Yulita Eka Fitri (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The aim of this study to determine the company's financial performance based on profitability ratios at PT. Pinus Merah Baturaja. This research uses types of quantitative descriptive research. This research uses a descriptive method to describe research objects or research results. The data in this research were collected through documentation, observation, and interviews. The gross profit margin analysis results show that in 2019, it was 13.9%, and the company experienced an increase in 2019, and in 2020 was 1.6% from the previous year and then increased return in 2021 by 0.4%. The company's net profit margin in 2019 was 4%, and the company experienced an increase in 2020 amounted to 0.2% from the previous year and then increased return in 2021 by 0.5%. Results of the return on assets analysis show that the company in 2019 was 11.8%, later experienced an increase in 2020 of 0.5% from the previous year and then increased again in 2021 by 0.6%. That matter shows that the company efficiently uses assets in each year. The return on equity analysis results show that in 2019, amounting to 33.7%, the company experienced an increase in 2020, which amounted to 1.3% from the previous year and increased again in 2021 by 4%. This happens because the company has been effective in managing the capital invested by the company to produce profits for the company.